Social debt in software development environments: A systematic literature review - Suárez-Brieva, Eydy; Pardo Calvache, César Jésus; Pérez-Castillo, Ricardo (Science of computer programming, 2026)
•Identifies five key sociothecnical factors where social debt emerges in agile and distributed teams.•Analyzes 45 primary studies on social debt in software development (2016-2024).•Proposes a taxonomy with 185 causes (62 in distributed teams, 38 in agile, 85 general) and 50 effects.•Classifies solutions into tools, theoretical models and predictive approaches.•Maps 35 community smells and their impact on the domains of social debt. Context: Lack of communication and coordination in a software development community can lead to short and long-term social problems. This can result in the misalignment of socio-technical congruence, understood as the disconnect between social and technical factors, which in turn leads to suboptimal decisions. The absence of adequate strategies to manage these problems, together with deficient organizational structures, favors the accumulation of social debt. Objective: This paper collects and analyzes studies related to the causes, effects, consequences, methods, patterns, domains, and prevention and management strategies of social debt in software development. While agile environments are included in the analysis, the overall focus covers a broader range of organizational and methodological contexts, including distributed, hybrid, and other team models. Method: A systematic literature review was conducted through a parameterized search in different databases. This allowed us to identify and filters 231 papers, of which 85 were considered relevant and 45 selected as primary studies. Results: The main socio-technical factors in which social debt is generated and exerts its impact were identified, along with a limited number of tools -mainly conceptual models and automated mechanisms- that facilitate its detection by defining potential causes affecting the well-being of the team and the companies. Conclusions: Based on the findings, it is important to further study other causes that allow identifying the presence of social debt, as well as the development of strategies to mitigate its effects on the social and emotional well-being of professionals.